2015
DOI: 10.1007/s12664-015-0571-6
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax after esophagectomy for esophageal cancer: Risk factors and management

Abstract: Difficult mediastinal dissection during esophagectomy in middle esophageal cancer may lead to thoracic duct injury. Complete response to NACRT may reduce the risk of chylothorax. Early transabdominal en masse ligation carries excellent results. Low output fistula following thoracic duct injury can be managed conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…found that patients with chylothorax had tumors in the middle third of the thoracic esophagus, and the usual site of injury to the thoracic duct was in the mid-thorax during mediastinal dissection (13). A similar finding was reported by Rao et al who found that the incidence of chylothorax in middle-third lesions was relatively higher than that in lower-third lesions (14).…”
Section: Discussionsupporting
confidence: 65%
“…found that patients with chylothorax had tumors in the middle third of the thoracic esophagus, and the usual site of injury to the thoracic duct was in the mid-thorax during mediastinal dissection (13). A similar finding was reported by Rao et al who found that the incidence of chylothorax in middle-third lesions was relatively higher than that in lower-third lesions (14).…”
Section: Discussionsupporting
confidence: 65%
“…Shah et al [ 18 ] found that it was associated with squamous cell carcinoma. Other risk factors include tumors located in the middle third of the esophagus [ 5 , 19 ] and positive lymph nodes [ 20 ]. Cervical anastomosis and neoadjuvant treatments were also considered as RFs [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al [ 5 ] found that patients with complete response to neoadjuvant treatment had reduced CHT, while middle third tumors had less. In our patients, the response to preoperative therapy was not statistically significant (p=0.42), while lower esophageal tumors had a better correlation (p=0.107).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of neoadjuvant therapy for the treatment of esophageal cancer on postoperative chylothorax incidence is unknown and controversial. Gupta et al [16] evaluated 45 patients with esophageal cancer who underwent esophagectomy after neoadjuvant chemoradiotherapy and reported that difficult mediastinal dissection during esophagectomy in middle esophageal cancer may result in thoracic duct injuries, and a complete response to neoadjuvant chemoradiation may reduce the risk of chylothorax. Gronnier et al [17] outlined the results from a European multicenter study and suggested that neoadjuvant chemoradiotherapy increased chylothorax rates, with a trend toward more cardiovascular and thromboembolic events.…”
Section: Risk Factors For Chylothoraxmentioning
confidence: 99%